1996
DOI: 10.1177/0145482x9609000107
|View full text |Cite
|
Sign up to set email alerts
|

The Auditory Skills Necessary for Echolocation: A New Explanation

Abstract: The study presented here explored theories that account for echolocation and established an audiometric test battery for blind persons that is designed to predict success in echolocation. Statistical analyses revealed significant positive correlations between particular auditory measures and echolocation performance. No relationships were found between high-frequency hearing sensitivity and echolocation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
2
13
0
2
Order By: Relevance
“…Results from the current study and others (Supa et al 1944 ; Carlson-Smith and Weiner 1996 ) show that auditory-guided locomotion is possible in an indoor environment, where room reverberation can sometimes benefit echolocation. Schenkman and Nilsson ( 2010 ) showed that echolocation detection performance was better in a reverberant room than in an anechoic room, possibly due to an “information surplus principle”, as changes in reverberation pattern offer a potential cue.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Results from the current study and others (Supa et al 1944 ; Carlson-Smith and Weiner 1996 ) show that auditory-guided locomotion is possible in an indoor environment, where room reverberation can sometimes benefit echolocation. Schenkman and Nilsson ( 2010 ) showed that echolocation detection performance was better in a reverberant room than in an anechoic room, possibly due to an “information surplus principle”, as changes in reverberation pattern offer a potential cue.…”
Section: Discussionsupporting
confidence: 69%
“…In summary, the aim of the current study was to build on and extend previous work investigating auditory-guided locomotion in indoor environments (Supa et al 1944 ; Strelow and Brabyn 1982 ; Carlson-Smith and Weiner 1996 ) by assessing the obstacle circumvention performance of blindfolded sighted echo-naïve participants generating mouth click sounds. Visually guided locomotion was used as a baseline.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use and acuity of echolocation have been studied quite extensively in several species (e.g. Carlson‐Smith & Wiener, 1996; Griffin & Suthers, 1970; Fenton, 1975, 1980; Medway & Pye, 1977; Griffin & Thompson, 1982; Suthers & Hector, 1982; Coles, Konishi & Pettigrew, 1987; Fullard et al ., 1993). However, as yet less attention has been paid to interspecific comparison of the structure of echo clicks.…”
Section: Introductionmentioning
confidence: 99%